The Challenges and Opportunities of Underprivileged Urbanized People in Accessing Education: A Case Study in Depok City - Asfiya’ R, M Syauqi; Windiana, Wiwin (UIII Press, 2024)
Urbanization is one factor influencing poverty in Indonesia’s major cities. Urbanization in Indonesia is characterized by migration of residents from villages to cities to improve their standard of living and try their luck in the city. However, many urbanized people who move from villages to cities need more education and specific skills. As a result, they need help to find easier and more decent jobs, even though cities provide more jobs. This condition causes many urbanized people to end up as underprivileged, such as street people busking at red lights and on the streets. This research aimed to examine the challenges and opportunities faced by underprivileged urbanized people in accessing education. The research used a qualitative case study approach. The participants in this study are urbanized people who move from villages to cities but end up being underprivileged in the cities they attend. Furthermore, the researchers used an interactive data analysis by Morse (1994), comprehending, synthesizing, theorizing and recontextualizing. The findings of this study are expected to provide a true picture of urbanized people and underprivileged people’s education. The results showed that the underprivileged urbanized people in Liu village, Depok face several challenges in fulfilling their education, such as difficulty enrolling their children in public school and paying school fees. Besides their opportunities to access education, they are already aware of government assistance, such as KIP and KDS programs, which allow them to pay their children’s tuition fees with LKS money.